Semiotics of Property Advertising on Social Media Facebook - Yunik Anggreni, Ni Putu; Rai Antara, I Made Agung (Jurnal Manajemen Pelayanan Hotel, 2022)
This study aims: (1) to find out and analyze from the semiotic aspect of verbal signs, visual signs, signifiers, and denotations of property advertisements on social media Facebook. (2) To determine the type of language style used in property advertisements in social media Facebook. The data source of this research is verbal form in the form of persuasive text contained in property advertisements on social media Facebook. The results showed that: (1) The parts contained in the advertisement were the title, company name, text, and symbols. The four parts are related to each other. The titles of the four advertisements are written in an ambiguous manner so as to arouse the curiosity of potential consumers to see the contents of the advertisement further. The relationship between signs and their references in the form of icons, indexes, and symbols in the analyzed advertisements can be found through semiotic analysis. The advertisement consists of a title, signature, text, and slogan. (2) The language style can be found in the title and text of the advertisement that after being analyzed, in the four advertisements can be found three kinds of language style ellipsis, repetition and asindenton Keywords: semiotics, advertising, language style, social media Facebook